Taskeater: An experience based study on the Client Management practices and processes of the company - Hamim, Mujtaba Nurul (BRAC University, 2016)
This thesis is restricted.This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2015